Effects of culture system and diet on amphipod (Parhyale hawaiensis) production - S. Laramore; E. Albright; C. Sinacore (Scientific Reports)
Abstract Amphipods have elicited interest for use as a live feed to culture marine species. However few studies have been conducted to determine optimal conditions necessary for large scale culture. The amphipod, Parhyale hawaiensis is a tropical species that has been considered for use in warm water marine culture. A 30 days study examined the effects of culture system and diet on amphipod production. Two culture systems (biofloc, clearwater) and three diets (fresh and dried Ulva lactuca, commercial shrimp diet) were compared. Water quality, and total adult, juvenile and hatchling densities were evaluated. Water quality was not significantly different between treatments, although a trend towards lower ammonia and nitrite levels were seen in biofloc systems. After 30 days, 50% of the population was comprised of juveniles, with adults and hatchlings each comprising 25% of the population. Total amphipod density differed significantly between treatments with highest density in the biofloc + fresh U. lactuca treatment and lowest density in the clear water + fresh U. lactuca treatment. Significant differences were seen in adult and juvenile populations, with higher densities noted in biofloc systems. Although no significant differences were seen with regards to diet, amphipods fed the U. lactuca diets showed more variation in density than those fed the commercial shrimp diet. Results of this study suggest that utilization of a biofloc culture system may both improve water quality and increase P. hawaiensis production. It is further suggested that more consistent production may been seen if amphipods are fed a commercial shrimp diet rather than a U. lactuca diet.